Status Unsur Hara Ca,Mg, dan S sebagai Dasar Pemupukan Tanaman Kacang Tanah (Arachis hypogaea L.) di Kecamatan Punung Kabupaten Pacitan - Sri Hartati; Joko Winarno; Grece Novarizki (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2012)
Title  : Nutrient Status Ca, Mg, and S as The Basic Fertilizing of The Groundnut (Arachis hypogaea L.) in Punung, Pacitan. The research was done in May until October 2008. The aims of this research were to know the status of soil N, P, K and determine the fertilizing and the soil management strategy for peanut in Punung, Pacitan. This research used fenomenological qualitative descriptive method that supported by laboratory analysis and cuisioner about agriculture activity by the farmers at Punung. The research soil variables are pH, organic-C, N total, P available, K available, CEC, base saturation, and soil tekstur. The result of this research shows that the globally available Ca soil  status in Punung is medium (6,08-7,87me%), avalaible Mg soil provided status globally is high(4,05-5,25me%) , and S soil provided status globally is also very low. S nutrient must be added Land Map Unit (LMU) 2, 5, 9, 14, 15 to reach yield 2 ton/ha and 2,5 ton/ha of groundnut. Soil management strategy is done by adding S fertilizer adjusted with the plant need by drowning it into the soil nearby the root area with two times fertilizing, ZA fertilizer addition to keep S supply, the addition organic matter, the use of mulsa, plant rotation and soil management adjusted tho the slope condition.